Stapled Bowel Anastomoses in Newborn Surgery - Kozlov, Yury; Novogilov, Vladimir; Podkamenev, Alexey; Weber, Irina (European Journal of Pediatric Surgery, 2013)
Background In this work, we have described our experience with repair of bowel discontinuity by applying stapled anastomosis. The aim of this study was to compare two basic intestinal anastomotic techniques and to establish the feasibility of the stapled connection of bowel in neonates and infants.Methods Between August 2009 and December 2011, we have performed 23 cases of hand-sewn anastomosis (group I) and 21 cases of mechanical anastomosis (group II) in children during the first 3 months of life. The standard hand technique was typically fashioned by continuous two-layer absorbable suture. A stapled anastomosis was accomplished using the linear endoscopic stapler with 2.5-mm staples (Ethicon Endo-Surgery, Cincinnati, Ohio, United States). The two groups were compared for patients' demographics, operative report, and postoperative outcomes.Results There were no differences in the preoperative parameters between the two groups regarding age before surgery, and body weight at operation. The “hand” group and “stapler” group had similar mean preoperative age (19.7 vs. 23.2 days; p = 0.096) and average weight (2884.3 vs. 2716.0 g; p = 0.692). The mean operative time for bowel continuity restoration in group I was 77.4 minutes. In contrast, the mean duration of the operation in the group II was 56.4 minutes. The differences between groups were statistically significant (p < 0.0001). The mean time of full enteral feeding for patients with mechanical anastomosis was isochronous for patients with standard hand-sewn technique (6.7 vs. 6.7 days; p = 0.926). The statistically identical postoperative hospital stay was registered in patients of both groups (13.3 vs. 14.1 days; p = 0.852). The postoperative course was uneventful in all the patients. All the anastomoses were fully functional at the end of the study.Conclusion Efficacy of the stapled anastomosis was confirmed by the shorter time of operation with saving of equal time of full enteral feeding and hospitalization.
Keywords: stapled intestinal anastomosis; newborn; children